Performance in Major League Baseball Pitchers After Surgical Treatment of Thoracic Outlet Syndrome. Issue 7 (30th July 2021) - Gutman, Brian; Hadley, Christopher; Kirsch, Jacob; Joyce, Christopher; Namdari, Surena; Gutman, Michael
Objectives: Thoracic outlet syndrome (TOS) can be a career threatening injury for baseball pitchers. The purpose of this study is to determine the efficacy of surgical management for TOS as a function of return to play and quantitative pitching metrics. Methods: Twenty-seven major league baseball pitchers underwent surgical treatment for TOS between January 2001 and December 2017. Analysis of pre and postoperative pitching metrics were used to assess the effect of surgery on 20 pitchers who returned to pitch in Major League Baseball (MLB). All pitching metrics were compared via assessing performance two years prior to surgery and two years after surgery. For 20 pitchers who returned to pitch, MLB pitching metrics of earned run average (ERA), walks plus hits per innings pitched (WHIP), wins above replacement (WAR), strikeouts per nine innings (K/9), average fastball velocity, and strike percentage, were used to assess a pitcher's ability to return to preoperative performance level. Results: Of the 27 pitchers, 20 pitchers were diagnosed with neurogenic thoracic outlet syndrome (NTOS) and seven with venous thoracic outlet syndrome (VTOS). The average age of onset of TOS was 28.6 years. There was no significant difference between the age of onset between the NTOS and VTOS populations (p=0.272). Of the 27 pitchers, 20 (74.1%) were able to return to MLB play at a mean of 297 days (range, 105-638 days) after surgery. Pitching metrics demonstrated that pitcher ERA remained inferior postoperatively compared to baseline preoperative performance (3.66 vs 4.50, p=0.03). Fastball velocity (p=0.94), strike percentage (p=0.50), and K/9 (p=0.878) were equivalent to pre-injury performance. There was no difference in preoperative pitching metrics between pitchers who were able to return and pitchers who were unable to return to the MLB. Conclusions: About 3/4 of professional pitchers who undergo surgical intervention for TOS are able to return to play at the MLB level. With regards to performance, the majority of metrics were unchanged from prior to surgery, indicating return at a similar functional level.